Indirect traumatic optic neuropathy. Issue 1 (December 2016) - Singman, Eric; Daphalapurkar, Nitin; White, Helen; Nguyen, Thao; Panghat, Lijo; Chang, Jessica; McCulley, Timothy
Abstract Indirect traumatic optic neuropathy (ITON) refers to optic nerve injury resulting from impact remote to the optic nerve. The mechanism of injury is not understood, and there are no confirmed protocols for prevention, mitigation or treatment. Most data concerning this condition comes from case series of civilian patients suffering blunt injury, such as from sports- or motor vehicle-related concussion, rather than military-related ballistic or blast damage. Research in this field will likely require the development of robust databases to identify patients with ITON and follow related outcomes, in addition to both in-vivo animal and virtual human models to study the mechanisms of damage and potential therapies.